Procedural implementation of the hospital integrated referral system (Sistem Rujukan Terintegrasi/ SISRUTE) in Indonesia: A systematic review - Septi Anggraini; Akhmad Ikhlasul Amal; Erna Melastuti (School of Health Sciences Al-Ma'arif, 2026)
Background: The Integrated Referral System (Sistem Rujukan Terintegrasi or SISRUTE) has been introduced in Indonesia to strengthen coordination, timeliness, and continuity of patient referrals across health care facilities. However, the available evidence remains dispersed across local studies and broader referral system literature. Objective: This review aimed to examine the procedural implementation of SISRUTE in hospitals in Indonesia and to identify the factors that influence its effectiveness, supporting conditions, and implementation barriers within referral service procedures. Methods: This study employed a systematic review design. Literature searches were conducted in Google Scholar, PubMed, ProQuest, and ScienceDirect using combinations of terms related to SISRUTE, patient referral, emergency referral, and hospitals. Studies published between 2021 and 2025, available in full text, and relevant to SISRUTE implementation in Indonesian health care settings were considered. Data from the included studies were extracted systematically and synthesized using a narrative approach. Results: Ten studies were included in the final review. The findings showed that SISRUTE and other digital referral systems generally improved referral efficiency, accelerated response time, and strengthened coordination between health facilities. Hospital-based evidence indicated that referral response commonly occurred within a short time frame, while digital referral implementation also contributed to improved workflow efficiency and user satisfaction. However, implementation remained constrained by limited bed capacity, inadequate infrastructure, uneven system integration, information quality issues, and variations in staff readiness. The review also found that performance expectancy, effort expectancy, and facilitating conditions influenced system use, whereas broader evidence emphasized the importance of interoperability, training, and organizational support. Conclusion: The procedural implementation of SISRUTE in hospitals in Indonesia shows substantial potential to improve referral management and service coordination. Nevertheless, the effectiveness of the system depends on technological readiness, institutional capacity, and sustained support for health workers. Strengthening infrastructure, integrating referral platforms with hospital service systems, and improving workforce preparedness are essential to optimize the contribution of SISRUTE to hospital referral quality in Indonesia.